A systematic review on management of chylous ascites following abdominal aortic aneurysm repair - Karthigesu Aimanan, MD, MRCS, DrSurg; Kaushik Ilango, MD; Ng Jun Jie, MBBS, MRCS, MMed, FRCSEd; Vikram Vijayan Sannasi, MB ChB, FRCS (JVS-Vascular Insights)
Background: Chylous ascites, a rare but significant complication of open abdominal aortic aneurysm (AAA) repair, involves the accumulation of triglyceride-rich lymph in the peritoneal cavity. Due to the limited data available from case reports and small series, establishing standardized diagnostic and management protocols remains challenging. Methods: This systematic review adhered to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for systematic reviews. A comprehensive literature search was conducted in the PubMed/MEDLINE, Cochrane Library, Scopus, and Web of Science databases up to October 2023. Eligible studies included case reports and case series documenting the management of chylous ascites after open AAA repair in adult patients. Data extraction focused on study characteristics, patient demographics, clinical presentation, management strategies, and outcomes. The quality of included studies was assessed using the Joanna Briggs Institute Critical Appraisal Checklists for case reports and case series. Results: A total of 22 studies (18 case reports and 4 case series) encompassing 27 individual patient cases were included. Conservative treatments, particularly total parenteral nutrition and dietary modifications, along with the addition of pharmacological agents such as octreotide and somatostatin, were effective in achieving the resolution of chylous ascites in 62% of cases. Surgical interventions were required in 10 patients (38%) after treatment failure. Among these, peritoneovenous shunting was performed in six patients, exploratory laparotomy with lymphatic ligation in eight patients, computed tomography lymphangiogram in three, and radiotherapy in one patient. Complications included severe pulmonary infection in two patients after re-exploratory laparotomy and shunt-related infections or mechanical failures in two patients. Overall, 26 of 27 cases (96%) achieved resolution of chylous ascites, whereas three cases (11%) resulted in death due to complications. Conclusions: Conservative management supplemented by pharmacological agents should be prioritized as first-line treatments for chylous ascites after open AAA repair. Surgical options should be reserved for refractory cases, with careful consideration of associated risks.